FENOMENA BULLYING DI PONDOK PESANTREN AL-HIKMAH KAJEN PATI (QUALITY, 2019)
The purpose of this study is to find out the forms of bullying behavior and to know the psychological dynamics of victims and perpetrators. This article uses a qualitative method with the object of research in Alhikmah Islamic Boarding School-Kajen, and the subject of this study there are four students and one board of students. As a result, there are bullying behaviors both verbal and non-verbal. Verbally including swearing, teasing, shouting, making negative labels, while non-verbally, including hitting, kicking, damaging his friend's belongings, forcing the will. In the psychological dynamics aspect of bullying victims, on average they are physically or at a school level less than the perpetrators, physically weaker, While the psychological dynamics of the bullying perpetrators are considering themselves to be superior, physically bigger and stronger, the perpetrators are happy with the spectacle of violence ( aggressive). Psychological dynamics in the context of the situation, including managers who are not responsive in fact all children, both large and small, are mixed without any sorting.